Strategic Leadership through Academic Supervision for Improving Graduate Quality in Pesantren based Madrasah - Syarifah Syahab; Akhmad Fauzi Hamzah (Edudeena : Journal of Islamic Religious Education, 2026)
Improving graduate quality has become a strategic priority for Islamic educational institutions in responding to increasingly complex educational demands. However, studies examining how strategic leadership is enacted through academic supervision in pesantren based madrasahs remain limited. This study aims to analyze how strategic leadership is implemented through academic supervision to improve graduate quality at an pesantren based madrasah. A qualitative case study design was employed at Madrasah Aliyah Pesantren Alkhairaat Mainatul Ilmi. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, vice principals, and students. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings reveal that strategic leadership is translated into a collaborative and mentoring-oriented academic supervision process aligned with the vision and values of the pesantren. This approach strengthens teachers’ professional efficacy, improves instructional quality, and contributes to better academic achievement and character development among students. The study concludes that integrating strategic leadership with adaptive academic supervision creates a sustainable mechanism for improving graduate quality. These findings contribute to the literature by demonstrating that the integration of value-based leadership and collaborative supervision within the unique culture of pesantren offers an effective model for enhancing educational quality in Islamic schools.